DESAIN MEDIA PEMBELAJARAN BIAYA PELUANG BERBASIS POWTOON DALAM MENINGKATKAN LITERASI DAN NUMERASI SISWA - Muslimah; Nizar Ahmad; Mustofa Nugroho (HAMKA INSIGHT, 2022)
The purpose of this research is to develop an animated video using Powtoon with the content of economic learning materials about opportunity costs so that students can understand the material in a way that is not boring, and students can achieve a level of mastery independently and increase student motivation in learning. The research method used in this research is Research and Development (R&D). The model used is the ADDIE model, but in this study the researcher only used the initial stage, namely the Analysis and Design stage. After conducting the analysis, the researcher conducted an opportunity cost learning design in the form of an animated video, with the first stage the researcher made a design framework using Microsoft Word and continued to design an animated video using Powtoon. From making animated videos, there are several parts that have been improved to get the best results. From the development that has been done, hopefully it can be useful for students so that they can achieve a level of mastery independently and increase learning motivation.